PENERAPAN SISTEM APLIKASI ABSENSI GURU BERBASIS WEB UNTUK MENINGKATKAN AKURASI DAN EFESIENSI ABSENSI DI SMP ISLAM NURUSH SHODIQIN - Nadiya Khairunisa; Nabila; Sultan Arkar; Wasis Haryono (Journal of Research and Publication Innovation, 2025)
Abstract-This research aims to develop and implement a web-based teacher attendance application system at Nurush Shodiqin Islamic Junior High School to improve accuracy and efficiency in managing attendance. The attendance process that has been done manually has various obstacles, such as recording errors, difficulty in monitoring attendance data, and inefficient use of time. Therefore, the implementation of a web-based application system is expected to overcome these problems by automating the attendance recording process, facilitating data access, and reducing human error. This application allows schools to manage teacher attendance more precisely and quickly, and provides attendance reports that can be accessed in real-time. The trial results show that this system has succeeded in improving the accuracy of attendance data and time efficiency in its management. Overall, the implementation of a web-based attendance application system at Nurush Shodiqin Islamic Junior High School has a positive impact in terms of more effective and efficient attendance management.